MANAGEMENT STRATEGY OF WAREHOUSE RECEIPT SYSTEM ON COCONUT COMMODITIES - Bustamin, Bustamin; Muluk, M. R. Khairul; Hermawan, Hermawan (Jurnal Aplikasi Manajemen, 2018)
Warehouse Receipt System is one of the most powerful tools to overcome price fluctuations in the agricultural/plantation sector, especially during the harvest season. Therefore, this study aims to analyze the existing conditions of coconut commodities in Inhil District and to formulate appropriate strategies for the application of WRS to the coconut commodities. Data were collected by observation, interview, and document review. Data were analyzed using interactive Miles, et al. (2014). Through Collection data, condensation data and finally withdrawing conclusions, then to create a strategy using SWOT analysis by compiling IFAS and EFAS tables. The study showed that the production of coconut commodities decreased dramatically, in which low coconut prices and fluctuation of the coconut prices were the main factors. While the result of suitable strategy is the diversification of strategy with the policy direction must be the master plan of WRS, acceleration of regional infrastructure development, strengthening of socialization of WRS, innovation of plantation water trio program through technology utilization and increasing industry in coconut processing sector.